The dragon awakes: Is Chinese competition policy a cause for concern? - Mario Mariniello (Bruegel, 2013)
China's Anti-Monopoly Law, adopted in 2007, is largely compatible with antitrust law in the European Union, the United States and other jurisdictions. Enforcement activity by the Chinese authorities is also approaching the level seen in the EU. The Chinese law, however, leaves significant room for the use of competition policy to further industrial policy objectives. The data presented in this Policy Contribution indicates that Chinese merger control might have asymmetrically targeted foreign companies, while favouring domestic companies. However, there are no indications that antitrust control has been used to favour domestic players. A strategy to achieve convergence in global antitrust enforcement should include support for Chinese competition authorities to develop the institutional tools they already have, and to improve merger control by promoting the adoption of a consumer-oriented test and enforcing M&A notification rules.
Keywords: 330; Monopol; Wettbewerbsrecht; Kartellrecht; Wettbewerbspolitik; China